Frequency Reconfigurable Circular Monopole Antenna with Key Shaped Ground Stub - Agarwal S.; Singh A.; Meshram M.K. (My University, 2025)
In this paper, a unique low profile double stubbed ground plane frequency reconfigurable circular monopole antenna is introduced. The ground plane contains two RF-PIN diodes that enable the antenna to be reconfigured in ultra-wideband (3.2–10.8 GHz) and dual frequency (2.8–4.01 GHz and 7.56–8.2 GHz) modes. The proposed antenna is designed using an FR-4 substrate with the dimension about 33×28×1.6 mm3. The impedance matching of the antenna at ultra-wideband operation is improved by a defected ground structure. The measured and simulated results of the antenna are in close agreement. This antenna is useful for cognitive radio application. © 2024, Electromagnetics Academy. All rights reserved.